Way to go: Mirroring real experiences of the escape rooms - Lim, Qian Pink; Darun, Mohd Ridzuan; Nawanir, Gusman; Chiam, Kee Swan (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Over the last decade, escape rooms have taken the entertainment industry by storm. Contenders sign up willingly, to be virtually locked up in unfamiliar rooms, with the understanding that they are in for an adventure of unravelling clues, puzzles and riddles as the clock ticks on them. While this phenomenon takes entertainment to the next level, the presence of escape rooms is extremely challenging in terms of continually catering to the appetites of a varied customer base. There are existing frameworks which touch on customer services, but unfortunately, none on this trade, which in fact, requires a lot of attention to ensure continuous growth and long term sustainability. This paper is an effort made to review our customers’ experiences in our escape rooms in Malaysia, to determine the constructs that are fundamental to enhancing customer experience in escape rooms in Malaysia. In addition, it functions to improve and design games suitable to their needs and most important for their frequent comebacks. This research was carried out in two establishments situated in Klang Valley, Malaysia. There were twenty contenders and they have met the criteria of at least a one-time involvement in the game. The study is qualitative in nature and it is advocated by using the sequential incident technique to excavate the customers’ perceptions which could be the base of our future Malaysian escape games. The analysis utilized is thematic and the results unearthed fifteen determinants in which nine are closely mirrored to the goaldirected behaviour model. The research benefits the discipline of customer experience mapping in this unique industry and the future escape room designs and enhancement for our escape rooms’ entrepreneurs.